Theoretical analysis of slip flow on a rotating cone with viscous dissipation effects - SALEEM, S.; NADEEM, S. (Journal of hydrodynamics. Series B, 2015)
This paper is concerned with the mutual effects of viscous dissipation and slip effects on a rotating vertical cone in a viscous fluid. Similarity solutions for rotating cone with wall temperature boundary conditions provides a system of nonlinear ordinary differential equations which have been treated by optimal homotopy analysis method（OHAM）. The obtained analytical results in comparison with the numerical ones show a noteworthy accuracy for a special case. Effects for the velocities and temperature are revealed graphically and the tabulated values of the surface shear stresses and the heat transfer rate are entered in tables. From the study it is seen that the slip parameter γ enhances the primary velocity while the secondary velocity reduces. Further it is observed that the heat transfer rate Nu Re-1/2x increases with Eckert number Ec and Prandtl number Pr.